Pesantren Curriculum Reformulation: Managerial Strategies to Improve Quality in Islamic Boarding Schools - Silviana, Nur Cholida; Husnan, Riayatul; Potimoh Jih Jih (IJIBS, 2025)
Curriculum reformulation in pesantren is a managerial strategy that is adaptive to the challenges of improving the quality of Islamic education in the contemporary era. This study aims to examine curriculum management at Pondok Pesantren At-Taqwa Ajung Jember, focusing on aspects of curriculum planning, implementation, and evaluation as a strategy to improve the quality of education. The approach used is qualitative with data collection methods through observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that curriculum planning at At-Taqwa Islamic Boarding School was carried out in a structured manner through: (a) organizing subject structures such as material mapping, textbooks, and scientific groupings; (b) preparing academic calendars, effective weeks, and annual activity programs; and (c) preparing learning tools, including syllabi, annual programs, semester programs, and lesson plans. Curriculum implementation is carried out through reviewing teaching tools and supervising learning activities to ensure effective implementation. Curriculum evaluation is carried out in stages: (a) input evaluation includes admission of new students and curriculum preparation; (b) process evaluation of learning implementation and supervision; and (c) output evaluation which includes learning outcomes and student achievement